Muhammad Zainuddin Abdul Madjid: The Pioneer of Islamic Education in Lombok Community West Nusa Tenggara, Indonesia - Azmi, Saadatul; Wardi, Faridatul (Khalifa Journal of Islamic Education, 2020)
This study aims to analyze the role of Muhammad Zainuddin Abdul Madjid as a prominent scholar and pioneer of Islamic education for the people of Lombok, West Nusa Tenggara Indonesia, and its relevance to modern education today. This study used a qualitative method with an individual life history approach. All data were collected through the character's curriculum vitae, literature, documentation, and evidence of the works left in writing and physically. Data collection is done by collecting, reducing, presenting, and closing with drawing conclusions. Overall, there are four clear pieces of evidence of Muhammad Zainuddin Abdul Madjid's role as a pioneer of Islamic education in Lombok society, first; founded the Nahdlatul Wathan Diniyah Islamiyah (NWDI) educational institution in 1937, second; the integration of the curriculum used refers to the style of education in the al-Saulatiyah Madrasah in Makkah, third; transition from classical to classical education (modern), fourth; the application of a tiered education system such as public schools such as the education model in the colonial period. With the establishment of educational institutions, the integration of the curriculum and the style of organizing this education, it has recorded a new history for the world of Islamic education in the people of Lombok, West Nusa Tenggara. The emergence of the renewal of Islamic education carried out by Muhammad Zainuddin Abdul Madjid has aroused the enthusiasm of the people of Lombok to establish various Islamic educational institutions with classical and modern styles.